Reassessing Particulate Organic Carbon Dynamics in the Highly Disturbed San Francisco Bay Estuary - Hernes, Peter J.; Dyda, Rachael Y.; Bergamaschi, Brian A. (Frontiers in Earth Science, 2020)
Environmental research has been shifting toward a new normal in which a primary focus is to capture change that may be accelerating. In this study, we collected particulate samples in the northern San Francisco Bay Estuary (SFBE) in the fall of 2011 through the spring of 2012 in order to assess vascular plant contributions across both time and space, and to compare our findings with a similar set of samples from 1990-92. Across the ~20-year span, we detected 1) decreasing C:Na ratios (averages±SD of 12.5±2.5 vs. 8.8±1.4, significant t-test with p<0.0001), 2) distinct shifts in chlorophyll vs. salinity, with higher chlorophyll concentrations shifting toward freshwater, and 3) greater relative proportions of vascular plant carbon that also appears less degraded (as indicated by lignin measurements) shifting from freshwater toward higher salinities. Lignin compositional data (syringyl:vanillyl and cinnamyl:vanillyl) suggests that increased lignin content in the more saline samples could be derived from wetland materials while a two-endmember mixing model indicates that a significant portion of the POC in the western sites (50-60% as an upper bound, 13-15% as a lower bound) could be wetland-derived. This has potential implications for the lower foodweb, given recent work that demonstrates selective feeding by copepods on wetland detrital material in the northern SFBE. The latter has ramifications for proposed wetland restoration within the SFBE and Sacramento River/San Joaquin River Delta system, namely that restored wetlands could confer important benefits toward the foodweb. Equally important is to prioritize continued monitoring of particulate organic matter cycling in the SFBE system to make sure that changing conditions are accounted for in any management decisions.